Mechanistic Insights Into MicroRNA-Induced Neuronal Reprogramming of Human Adult Fibroblasts - Lu, Ya-Lin; Yoo, Andrew S. (Frontiers in Neuroscience, 2018)
The use of transcriptional factors as cell fate regulators are often the primary focus in the direct reprogramming of somatic cells into neurons. However, in human adult fibroblasts, deriving functionally mature neurons with high efficiency requires additional neurogenic factors such as microRNAs (miRNAs) to evoke a neuronal state permissive to transcription factors to exert their reprogramming activities. As such, increasing evidence suggests brain-enriched miRNAs, miR-9/9* and miR-124, as potent neurogenic molecules through simultaneously targeting of anti-neurogenic effectors while allowing additional transcription factors to generate specific subtypes of human neurons. In this review, we will focus on methods that utilize neuronal miRNAs and provide mechanistic insights by which neuronal miRNAs, in synergism with brain-region specific transcription factors, drive the conversion of human fibroblasts into clinically relevant subtypes of neurons. Furthermore, we will provide insights into the age signature of directly converted neurons and how the converted human neurons can be utilized to model late-onset neurodegenerative disorders.